Development of Health Tourism in West Pomeranian Voivodeship - Elżbieta Sieńko-Awierianów (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2020)
Health resort treatment is an important element of the Polish health care system. An aging population, an increase in the amount of free time and income, as well as a healthy lifestyle trend are the main factors for the development of health tourism. West Pomeranian voivodeship ranks 3rd in the country in terms of the number of health resorts, as well as is the undisputed leader in terms of the number of people visiting Polish resorts. In 2017, over 25% of patients underwent medical treatment in health resorts in West Pomeranian voivodeship. The aim of the study was to analyze the potential of health resorts in West Pomeranian voivodeship and to assess the development of tourist traffic in health resorts in recent years. West Pomeranian voivodeship observes a steady increase in the number of health resort visitors using the services offered by health establishments and a changing structure of patients in regard to the financing method - there is a growing number of people who finance their stay in the health resort on their own. In order to maintain the leading position on the market of health tourism services, it is necessary to raise the standard of health services, carry out further investments in modern health resort infrastructure that is open to innovative and unconventional solutions combining traditional and modern methods of treatment as well as preventive healthcare and leisure. There is a need to constantly adapt the health tourism product to the changing needs of patients and to create new brand of products as well as acquire new groups of recipients who finance their stay in health establishments.